Governance Synergy in Developing Sustainable Tourism in Pati Regency Indonesia - Endhartiko, Tigran (Journal of Public Administration Studies, 2016)
This study aims to analyze and to describe (sustainable) tourism development in Pati Regency as well as the roles of each tourism stakeholders within, by using qualitative research method. This research utilized both primary and secondary data. This study found that tourism development in Pati Regency is still in the early stage of development however, it is potential to be further developed toward sustainability, because the basic principles of sustainable tourism are already exist in which tourism stakeholders in are actively participates in the tourism development and coordination among them is present as well. Moreover, through decentralization and participatory development implementation, Pati regency tourism development is in the right direction toward sustainability.